Simulation and optimization of butane autothermal reformer for fuel cell applications - Abdullah, Mohd. Shahir (2006)
Hydrogen (H2) production has gaining popularity among researchers to aim a better future environment. H2 is very excellent candidate to replace the existing fuel. Its high flammability and energy produced alongside no side product generated make it even more popular. The objective of the study is to develop a general steady-state simulation of H2 production plant for fuel cell application using butane as the feedstock. The scopes of the study include stoichiometry mathematical calculations, base case steady-state simulation, base case simulation validation, a design of heat integration, carbon monoxide (CO) clean-up processes which contains water gas shift (WGS) and preferential oxidation (PrOx) reactors and plant wide optimization. The simulation has been run in Aspen HYSYS 2004.1 in steady-state mode in which optimization was done to generate more H2 as well as CO reduction. The butane fuel processor was optimized at O/C ratio of 2.18 and S/C ratio of 4.6 to produce 39.2% of H2 and has achieved 78.1% efficiency. While CO clean-up units was capable to reduce the CO concentration down to 10 ppm.